Outcome after pediatric liver transplantation for staged abdominal wall closure with use of biological mesh—Study with long‐term follow‐up. (12th March 2020) - Gül‐Klein, Safak; Dziodzio, Tomasz; Martin, Friederike; Kästner, Anika; Witzel, Christian; Globke, Brigitta; Jara, Maximilian; Ritschl, Paul Viktor; Henning, Stephan; Gratopp, Alexander; Bufler, Philip; Schöning, Wenzel; et al.
Abstract: Abdominal wall closure after pediatric liver transplantation (pLT) in infants may be hampered by graft‐to‐recipient size discrepancy. Herein, we describe the use of a porcine dermal collagen acellular graft (PDCG) as a biological mesh (BM) for abdominal wall closure in pLT recipients. Patients <2 years of age, who underwent pLT from 2011 to 2014, were analyzed, divided into definite abdominal wall closure with and without implantation of a BM. Primary end‐point was the occurrence of postoperative abdominal wall infection. Secondary end‐points included 1‐ and 5‐year patient and graft survival and the development of abdominal wall hernia. In five out of 21 pLT recipients (23.8%), direct abdominal wall closure was achieved, whereas 16 recipients (76.2%) received a BM. BM removal was necessary in one patient (6.3%) due to abdominal wall infection, whereas no abdominal wall infection occurred in the no‐BM group. No significant differences between the two groups were observed for 1‐ and 5‐year patient and graft survival. Two late abdominal wall hernias were observed in the BM group vs none in the no‐BM group. Definite abdominal wall closure with a BM after pLT is feasible and safe when direct closure cannot be achieved with comparable postoperative patient and graft survival rates.